Effect of restricted suckling on the growth performance of Hampshire piglets* (Indian Journal of Animal Production and Management, 2024)
Eighteen Hampshire sows with their litters were randomly selected and divided into three groups keeping similar parities and equal average body weight of dams and their piglets in each group from 4th week onwards such as unrestricted suckling (T1), 6 hours restricted suckling (T2) and 12 hours restricted suckling (T3) groups.All the animals were reared under standard feeding and management conditions. Weaning of piglets was done at 8th week of age. The average body weight of piglets at 8th week was 9.66±0.39, 10.48±0.19 and 12.00±0.22 kg in T1, T2 and T3 groups, respectively. The average daily body weight gain of piglets from 4th  to 8th week of age was 0.139±0.01, 0.164±0.01 and 0.220±0.01 kg in T1, T2 and T3 groups, respectively. There was highly significant difference (P
Keywords: Cost of feeding; Growth; Hampshire; Piglets; Restricted suckling